Evaluation of IgE Antibodies to Omalizumab (Xolair®) and Their Potential Correlation to Anaphylaxis - Baker, Dana L. (AAPS J, 2015)
Omalizumab (Xolair®) is a recombinant humanized monoclonal antibody that selectively binds to human immunoglobulin E (IgE). Omalizumab is used to treat IgE-mediated diseases such as chronic idiopathic urticaria (CIU) and moderate to severe allergic asthma. In pre-marketing clinical trials in patients with asthma, anaphylaxis was reported in 3 of 3,507 (0.1%) patients. In post-marketing spontaneous reports, the frequency of anaphylaxis attributed to omalizumab use was estimated to be at least 0.2% of patients based on an estimated exposure of about 57,300 patients from June 2003 through December 2006. To better understand the risk of anaphylaxis in patients with allergic asthma receiving omalizumab, a post-marketing pharmacosurveillance study was initiated in 2009. As part of this study, an assay was developed to detect antibodies of IgE isotype to omalizumab. Serum samples from patients in the study were evaluated using this assay. Our results indicated that there was no observable correlation between either anaphylaxis or skin test reactivity and the presence of antibodies of IgE isotype to omalizumab. Here, we discuss the development of this assay as well as the results of the immunogenicity assessment.